Work Motivation, Organizational Culture, and Work Satisfaction as a Moderator of The Effect of Participation in Budgeting Toward Managerial Performance - Tun Huseno (Management Institute Faculty of Economics Universitas Andalas, 2021)
This study identifies how participation in budgeting affects performance in managerial. The moderating variables analyzed are work motivation, the culture of organization and work satisfaction while the sample involved in this research is the Regional Apparatus Organization (OPD) of the City of Bukittinggi, West Sumatera, Indonesia. The results show that participation in budgeting has a positive effect on the performance in managerial aspect; organizational culture and work satisfaction control the influence of participation in budgeting on the performance in managerial in the City Government of Bukittinggi, however work motivation does not moderate the influence of participation in budgeting on the performance in managerial in the City Government of Bukittinggi.